2016
DOI: 10.3892/ijo.2016.3738
|View full text |Cite
|
Sign up to set email alerts
|

HOXB4 knockdown reverses multidrug resistance of human myelogenous leukemia K562/ADM cells by downregulating P-gp, MRP1 and BCRP expression via PI3K/Akt signaling pathway

Abstract: Multidrug resistance (MDR) plays a pivotal role in human chronic myelogenous leukemia (CML) chemotherapy failure. MDR is mainly associated with the overexpression of drug efflux transporters of the ATP-binding cassette (ABC) proteins. Phosphoinositide 3-kinase (PI3K)/Akt signaling cascade is involved in the MDR phenotype and is correlated with multidrug resistance 1 (MDR1)/P-glycoprotein (P-gp), multidrug resistance-associated protein 1 (MRP1) and breast cancer resistance protein (BCRP) expression in many huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
4
31
1
Order By: Relevance
“…Therefore, it was deduced that baicalin reduces resistance to ADM by increasing the intracellular accumulation of ADM in HL-60/ADM cells. Our results are in accordance with previous studies [16,17] (Fig. 3).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Therefore, it was deduced that baicalin reduces resistance to ADM by increasing the intracellular accumulation of ADM in HL-60/ADM cells. Our results are in accordance with previous studies [16,17] (Fig. 3).…”
Section: Discussionsupporting
confidence: 94%
“…3). It has been reported that administration of osthol [17] or suppressing the expression of the HOXB4 gene [16] increases the intracellular accumulation of ADM in K562/ADM cells. The consistent results from studies using different treatments and different ADM-resistant cell lines suggested that increasing the intracellular levels of ADM is a common mechanism of combination therapy with ADM, reversing resistance to ADM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MDR is a major cause of failure of prostate cancer chemotherapy and is associated with an increased mortality risk (53). The PI3K/Akt signaling cascade may be correlated with MDR1/P-glycoprotein (P-gp) and plays a critical role in Figure 1.…”
Section: Abca1 and Multidrug Resistance (Mdr)mentioning
confidence: 99%